The Autonomy of Imagination in the Second Edition of Kant’s Critique of Pure Reason: A Critique of Heidegger’s Interpretation from the Perspective of the Critique of Judgement - Rodríguez, Manuel Sánchez (Pensamiento. Revista de Investigación e Información Filosófica, 2014)
This paper deals with the role played by imagination in the Transcendental Deduction argument from Kant’s Kritik der reinen Vernunft, focusing particularly on the differences between the 1781 and 1787 editions. My aim is to put into question the starting point of Heidegger’s interpretation presented in Kant und das Problem der Metaphysik. In contrast I will provide a construal of both editions,according to which it is actually in the second edition where Kant reached a proper understanding of the autonomy of imagination in the argument. If the first edition best owed such an important role on this faculty, it is because Kant still had not distinguished sharply between the subjective and the objective dimensions of its activity in the process of knowledge, as would be remarkably revealed if one were to pay a close attention to Kant’s «aesthetic project» in the 1780’s. In contrast, in the 1787 edition, Kant focused only on the determining activity of imagination qua transcendental, as long as the Deduction is to prove merely the objective validity of knowledge. Against Heidegger, I claim that such exclusio of the subjective and sensible dimension of imagination in the Kritik der reinen Vernunft is due to the fact that in 1787 Kant had found a new place to tackle this question with in the general frame work of the critical foundation of metaphysics, namely, the Kritik der Urteilskraft.